Influence of powder particle size on the microstructure of a hot isostatically pressed superalloy - Qu, Zonghong; Zhang, Pingxiang; Lai, Yunjin; Wang, Qingxiang; Song, Jiaming; Liang, Shujin (Journal of materials research and technology, 2022)
The influence of powder particle size on the microstructure of the powder metallurgy superalloy FGH97 was investigated. The powder atomized by the plasma rotating electrode process was sieved to three types: fine powder (0–53 μm), medium-sized powder (53–150 μm), and coarse powder (150–212 μm), which were all characterized by their nearly perfect spherical shape and low oxygen content. The powder was filled, degassed, sealed, and then densified by hot isostatic pressing. Then the microstructures of the fully dense compacts were characterized. The results show that fine powder led to limited plastic deformation of particles during densification, resulting in a minimum of Σ3 boundaries and modest PPB (Previous Particle Boundary) decoration. The fine powder compact showed that low impact toughness was caused by fracture along the PPB. However, the addition of Nb and Hf promoted the formation of the dispersed stable MC particles inside the grain, thus preventing the diffusion of C to the surface of the powder particles to form M6C carbides, and resulting in little tendency to present PPB for this alloy. Therefore, the medium-sized powder and coarse powder compact did not present PPB. Thus, the medium-sized powder is optimal for HIP compact preparation, given that fine powder produced PPB while the coarse powder increased the grain size.